Mga kagamitang panturo para sa isahang paglinang ng mga kasanayan sa pakikinig (aural discourse) ng mga mag-aaral sa unang taon sa kolehiyo - Coronel, Ester Espiritu 1935- (1977)
This seminar paper attempted to present the design and development phases in the preparation of aural discourse materials. A survey and examination of instructional materials currently available in Pilipino at the college level were conducted so as to have valid justification for the design of a new set of learning materials. The learning materials were subjected to an internal evaluation to determine the workability of the materials in actual classroom situations.